Curcumin Alleviates H₂O₂-Induced Oxidative Damage in Caco-2 Cells by Modulating Antioxidant Enzymes and Tight Junction Proteins - Kose, Tugba (International Journal of Innovative Research in Medical Science, 2025)
Background/Objectives: The intestinal epithelium is a one-cell-thick layer lining the mucosal surface that both absorbs nutrients from food and serves as a barrier to maintain mucosal integrity. Impairment of intestinal barrier integrity allows the passage of excluded substances, which induce various gastrointestinal disorders like inflammatory bowel disease (IBD). Accordingly, intestinal health and diseases are highly associated with intestinal barrier integrity and function, which are regulated by the mucous layer and tight junction structures of epithelial cells. Therefore, this study was dedicated to investigating the effect of hydrogen peroxide (H2O2) as an oxidative stress inducer as well as focusing on the antioxidant effects of the natural product curcumin (Cur) against oxidative stress in Caco-2 cells. Methods: Caco-2 cells were treated with 10 μmol/L Cur and then exposed to 250 μmol/L H2O2. Caco-2 cell viability was measured by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyltetrazolium bromide (MTT) assay, Reactive Oxygen Species (ROS) were detected by dihydrodichlorofluorescein (H2DCF) cell-permeant probe. Cu/Zn superoxide dismutase (SOD) activities, Catalase (Cat), glutathione (GSH) levels, lipid peroxidation, mRNA, and Western blot were assayed with commercially available kits. Results: Cur enhanced the viability of H2O2-treated Caco-2 cells in a dose-dependent manner. H2O2-treated Caco-2 cells exhibited the elevated levels of depletion in GSH, SOD and Cat activities, ROS productions, and lipid peroxidation while Cur reversed the H2O2-induced oxidative stress effects. The treatment of H2O2-induced Caco-2 cells with Cur improved the mRNA gene and protein levels of claudin-1 and glutathione peroxidase 4 (GPX4). Conclusions: The protective effects of Cur against H2O2-mediated oxidative damage in intestinal Caco-2 cells may be mediated through the GSH pathway.